Countess Eleonora: A prominent donator and benefactor from the Patačić noble family - Jasmina Lukec (Studia Lexicographica)
The article explores the influence and significance of Countess Eleonora Patačić, the last member of her family, in Croatian cultural history. As the daughter of Katarina Patačić, known in Croatian literary historiography for commissioning and editing the collection Pesme horvatske (1781), the first published secular work in Croatian literature featuring an editor with a female name and the most important collection of secular poetry in the Kajkavian literary tradition of the 18th century, and as the wife of Bartol Patačić, a figure of high political importance who enjoyed »universal respect and love« among the people, Eleonora dedicated her life to philanthropic endeavours. Drawing upon available literature and archival research, including material from the personal archive of Josip Matasović and mostly anonymous manuscript poems of occasional nature dedicated to Eleonora, her husband Bartol, and her identically named mother-in-law, the article highlights Eleonora’s philanthropic work. This includes monetary contributions towards the construction of religious buildings, the erection of tombstones for family members, and the donation of an inherited family library to today’s National and University Library in Zagreb on two occasions. Furthermore, her charitable role is exemplified by the establishment of the oldest Croatian charitable association in Varaždin in 1828, and her will stipulated the allocation of monetary funds to the needy on numerous family estates. Following her husband Bartol’s death in 1817, she also fulfilled his vision of establishing a foundation to aid serfs, leaving them estates in Vidovec, Guščerovec, Kalnik, and Martijanec. Recognised as a philanthropist and a lover of the national language, works were dedicated to her by Josip Vračan (1823), Filip Smolec (1823), and Dragutin Rakovac (1831 and 1832). The article presents transcribed excerpts from these works as well as several anonymous occasional poems addressed to Eleonora and her family members on the occasion of their name days and birthdays.